2016
DOI: 10.1152/physiolgenomics.00110.2015
|View full text |Cite
|
Sign up to set email alerts
|

Peptide affinity analysis of proteins that bind to an unstructured NH2-terminal region of the osmoprotective transcription factor NFAT5

Abstract: NFAT5 is an osmoregulated transcription factor that particularly increases expression of genes involved in protection against hypertonicity. Transcription factors often contain unstructured regions that bind co-regulatory proteins that are crucial for their function. The NH2-terminal region of NFAT5 contains regions predicted to be intrinsically disordered. We used peptide aptamer-based affinity chromatography coupled with mass spectrometry to identify protein preys pulled down by one or more overlapping 20 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 57 publications
(91 reference statements)
3
20
0
Order By: Relevance
“…All of these findings suggested that HuR may play a crucial role in maintaining ECM homeostasis in NP cells, a function of HuR that has yet to receive much attention and may have important implications for cancer cell metastasis and tissue fibrosis. Recent data suggest that HuR binds to TonEBP, an osmosensitive transcription factor TonEBP (NFAT5) that is one of the important regulators of ECM homeostasis in the NP niche [58][59][60][61][62]. Considering that HuR does not stabilize Hif-1α in NP cells, it is plausible that HuR's actions on ECM could occur through regulation of TonEBP activity or other key transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…All of these findings suggested that HuR may play a crucial role in maintaining ECM homeostasis in NP cells, a function of HuR that has yet to receive much attention and may have important implications for cancer cell metastasis and tissue fibrosis. Recent data suggest that HuR binds to TonEBP, an osmosensitive transcription factor TonEBP (NFAT5) that is one of the important regulators of ECM homeostasis in the NP niche [58][59][60][61][62]. Considering that HuR does not stabilize Hif-1α in NP cells, it is plausible that HuR's actions on ECM could occur through regulation of TonEBP activity or other key transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…extract, 232 in the nuclear extract, and 41 in both. We previously identified 152 of the 351 proteins in our study (9) of the NH 2-terminal region of NFAT5.…”
Section: Proteins Associated With the Nfat5 Peptide Baitsmentioning
confidence: 87%
“…The present experiments used peptide baits directed at a COOHterminal intrinsically disordered region of NFAT5 to identify proteins that associate with that region. Other than that, the experimental and analytical methods are largely the same as those used in our previous paper directed at the NH 2-terminal intrinsically disordered region of NFAT5 (9) and are briefly summarized as follows:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations